An enchanted ring and a Dung Beetle: contaminated borders in Hassan Blasim's nightmarish narratives. Issue 2 (2nd September 2018) - Al-Masri, Khaled
ABSTRACT: I analyze Iraqi author Hassan Blasim's "The Nightmares of Carlos Fuentes" and "The Dung Beetle, " two short stories that are centrally concerned with the border crossing experiences of Iraqi immigrants and refugees residing in Europe. In both stories, Blasim's protagonists try to suppress past trauma and forge new identities rooted solely in the present. And yet their trauma resurfaces in the space of dreams and in the narrative itself, manifesting itself as literary madness. I employ the term "contamination" to describe how the experience of border crossing leaves its mark, altering the body, mind, identity, and narrative of the border crosser. Intentionally referencing the racism, xenophobia, and religious bigotry that inform the myth of national purity and its perceived defilement by border crossers, "contamination" is inherent to the creation of so-called "diaspora spaces, " where multiple subjectivities intersect and, however contentiously, co-exist.